Imposter Syndrome: Doubting Success - Imran, Rayaan; Ali, Mohsan; Shuja, Muhammad Hamza (Journal of the Pakistan Medical Association, 2023)
Dear Madam, Imposter syndrome is defined as the psychological experience in which one believes that their accomplishments were purely due to chance and not based on merit(1). It is no shock that this phenomenon is common in a highly competitive and intellectually demanding medical career. This syndrome not only strives amongst medical students, but also amongst physicians far ahead in their careers(2). A recent study has demonstrated that mental illnesses and their associated phenomena are present in 21.0% of the adults in the United States(3). The results of this study are a reason for concern, especially amongst students in Pakistan, where experiences such as the imposter syndrome contribute to the already poor mental health and access to mental health treatments(4). This form of self-doubt results in a decline in emotional paralysis and a decline in productivity and confidence(5). A detailed online literature search on PakMediNet and PubMed surprisingly resulted in no articles addressing the occurrence of imposter syndrome and its adverse effects on Pakistani students, demonstrating the severe lack of attention given to this phenomenon. Medical students exhibit high-stress levels and self-doubt(6), but no diagnosis is ever reached. Therefore, the need of the hour is to conduct studies regarding imposter syndrome in medical schools. Since the field of medicine is highly romanticized in Pakistan, people are not enlightened regarding these aspects among medical students, especially the ones in top medical schools, as well as the high achievers. Furthermore, it is pivotal for medical institutions to bring forth and initiate programs that empower the members of the healthcare profession to recognize and address this phenomenon. In addition, easy access to therapy and/or counselling sessions provided by medical educational programmes shall allow medical students to enhance their overall mental health. It shall contribute to decreasing cases of psychological illness and social isolation. Medical educators must also realize that it is not only the underperforming learner who struggles and needs support but also those who are far ahead in their medical careers. The participation of parents is also imperative; they must be made aware of this syndrome to allow them to identify the possible signs of the syndrome on a personal level. Encouraging students to celebrate their successes, share their thoughts, and accept the presence of the imposter syndrome will promote a healthier social and academic lifestyle producing good quality members of the healthcare system of Pakistan.